Polaritons em materiais magnéticos nanoestruturados - Araújo, Carlos Alexandre Amaral (2007)
In this work we present a theoretical study about the properties of magnetic polaritons in superlattices arranged in a periodic and quasiperiodic fashíons. In the periodic superlattice, in order to describe the behavior of the bulk and surface modes an effective medium approach, was used that simplify enormously the algebra involved. The quasi-periodic superlattice was described by a suitable theoretical model based on a transfer-matrix treatment, to derive the polariton's dispersion relation, using Maxwell's equations (including effect of retardation). Here, we find a fractal spectra characterized by a power law for the distribution of the energy bandwidths. The localization and scaling behavior of the quasiperiodic structure were studied for a geometry where the wave vector and the external applied magnetic field are in the same plane (Voigt geometry). Numerical results are presented for the ferromagnet Fe and for the metamagnets FeBr2 and FeCl2